Prophylactic Cefazolin Dosing in Women With Body Mass Index >35 kg·m−2 Undergoing Cesarean Delivery: A Pharmacokinetic Study of Plasma and Interstitial Fluid. (July 2020) - Eley, Victoria A.; Christensen, Rebecca; Ryan, Rochelle; Jackson, Dwane; Parker, Suzanne L.; Smith, Matthew; van Zundert, Andre A.; Wallis, Steven C.; Lipman, Jeffrey; Roberts, Jason A.
Abstract : BACKGROUND: Obesity is a risk factor for surgical site infection after cesarean delivery. There is inadequate pharmacokinetic data available regarding prophylactic cefazolin dosing in obese pregnant women. We aimed to describe the plasma and interstitial fluid (ISF) pharmacokinetics of cefazolin in obese women undergoing elective cesarean delivery and use dosing simulations to predict optimal dosing regimens. METHODS: Eligible women were scheduled for elective cesarean delivery at term, with a body mass index (BMI) of >35 kg·m −2 . Plasma and ISF samples were collected following 2 g of intravenous cefazolin. Concentrations were determined using liquid chromatography-mass spectrometry. Population pharmacokinetic modeling and Monte Carlo dosing simulations were performed using Pmetrics. Total and unbound cefazolin concentrations in plasma and ISF were compared with the minimum inhibitory concentration at which 90% of isolates are inhibited (MIC90 ) of cefazolin for Staphylococcus aureus, 2 mg·L −1 . The fractional target attainment (FTA) of dosing regimens to achieve a pre-established target of 95% unbound ISF concentrations >2 mg·L −1 throughout a 3-hour duration of the surgery was calculated. RESULTS: The 12 women recruited had a median (interquartile range [IQR]) BMI of 41.5 (39.7–46.6) kg·m −2 and a median (IQR) gestation of 38.7 weeks (37.9–39.0). For each timepoint up to 180 minutes, the median across subjects of total and unbound plasma concentration of cefazolin remained above 2 mg·L −1 . The minimum observed total plasma concentration was 31.7 mg·L −1 and plasma unbound concentration was 7.7 mg·L −1 (observed in the same participant). For each timepoint up to 150 minutes, the median across subjects of unbound ISF concentrations remained above 2 mg·L −1 . The minimum observed unbound ISF concentration was 0.7 mg·L −1 (observed in 1 participant). In 2 participants, the ISF concentration of cefazolin was not maintained above 2 mg·L −1 . The mean (± standard error [SE]) penetration of cefazolin (calculated as area under the concentration-time curve for the unbound fraction of drug [ f AUC]tissue / f AUCplasma ) into the ISF was 0.884 ± 1.11. Simulations demonstrated that FTA >95% was achieved in patients weighing 90–150 kg by an initial 2 g dose with redosing of 2 g at 2 hours. FTA was improved to >99% when an initial 3 g dose was repeated at 2 hours. CONCLUSIONS: To maintain adequate ISF antibiotic concentrations in obese pregnant women, our results suggest that redosing of cefazolin may be required. When wound closure has not occurred within 2 hours, redosing is suggested, following either a 2 or 3 g initial bolus. These preliminary results require validation in a larger population.